Formulation and Evaluation of Nanoemulsion for Topical Application - Ravi, Saranya; Ponnusamy, Sutha; Balakrishnan, Sangameswaran; Karuppusamy, Nithyapriya; Bheeman, Saranya; senthilkumar, Yuvashree (Journal of Neonatal Surgery, 2025)
Advanced drug delivery methods known as nanoemulsions are distinguished by their minuscule droplet sizes, which are usually between 20 and 200 nanometers. These submicron emulsions have shown great promise as topical drug delivery vehicles, especially for medications with low solubility in water. When applied to the skin, their distinct physicochemical characteristics—such as high surface area, optical transparency, kinetic stability, and improved permeation—can greatly increase the solubility, bioavailability, and therapeutic efficacy of lipophilic medications. The different formulation and assessment characteristics of nanoemulsions meant for topical administration are the main topics of this review paper. In order to determine the stability, droplet size, and drug loading efficiency of the nanoemulsion, it examines the strategic selection of formulation ingredients such as oils, surfactants, and co-surfactants. The preparation processes are covered in detail, with a focus on high-energy and low-energy emulsification methods and their significance in reaching the appropriate droplet size and stability profile. To assess the caliber and functionality of the created formulations, characterization methods including droplet size analysis, zeta potential measurement, pH determination, viscosity testing, and thermodynamic stability investigations are examined. In order to validate the effectiveness and safety of topical nanoemulsions, the study also highlights in vitro and in vivo evaluation metrics such drug release profiles, skin permeation tests, and skin irritation assessments. The ultimate goal of this analysis is to present a thorough understanding of topical delivery systems based on nanoemulsions, bolstering their potential for use in cosmetic and dermatological treatments